Model Mushaf Al-Qur’an Berwarna Di Indonesia: Antara Perspektif Hukum Islam dan Komodifikasi Agama - Irsyadi, Najib (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2024)
At the beginning of the decade of the 3rd millennium, starting from 2005, the development of the Al-Qur'an mushaf in Indonesia experienced striking innovation. Different from the previous era, in this one many the Al-Qur'an mushafs have emerged with colored displays, such as cover designs, illuminations, paper, writing, verse blocks, and variations in its content. Apart from being supported by advanced computerization of the mushaf, another main factor is the changing tastes of the Indonesian Muslim community. This raises the question, how Islamic law's view of addressing this phenomenon, and how the colored mushaf model is seen from the perspective of religious commodification. By using descriptive-qualitative methods and a sociological-historical approach, this paper wants to answer the problem. The majority of Muslim scholars from moderate circles, such as Imam An-Nawawi and the Egyptian Fatwa Institute, allow the colored mushaf with the aim of providing information on the law of reading in its mushaf and increasing motivation to always read it. Meanwhile, textualist-normative scholars tend to prohibit the mushaf that is decorated or colored with hadith evidence. The widespread circulation of the colored mushaf, if analyzed based on the theory of religious commodification, has at least three elements: First, profit; The business of selling the Qur'anic mushaf always looks at market share that can promise financial profits. Second, knowledge transfer; every expression, idea, symbol can be transformed to other people in concrete form through a product that can be enjoyed or sold. Third, ideology; The Qur'anic mushaf printing industry has formed a commodity in Islam which contains certain religious understandings so that these understandings develop and become real.